Dislocation analysis of InGaN/GaN quantum dots grown by metal organic chemical vapor deposition. (November 2016) - Yang, Di; Wang, Lai; Hao, Zhi-Biao; Luo, Yi; Sun, Changzheng; Han, Yanjun; Xiong, Bing; Wang, Jian; Li, Hongtao
Abstract: The dislocations in InGaN/GaN quantum dots grown by metal organic chemical vapor deposition were studied by high-resolution transmission electron microscopy combining the Fourier filtering process. The misfit dislocations were observed in uncapped InGaN/GaN quantum dots. However, for the capped InGaN/GaN quantum dots, the GaN capping layer was found to suppress the generation of misfit dislocations and hence hindered the strain relaxation. Therefore, an overgrowth InGaN layer was used to relieve the strain in InGaN quantum dots and misfit dislocations were correspondingly found in these samples. In addition, defects were observed in low temperature GaN layers which suggested the existence of stacking faults. Highlights: The dislocations in InGaN/GaN QDs grown by MOCVD were studied by HRTEM combining the Fourier filtering process. The GaN capping layer was found to suppress the generation of misfit dislocations and hence hindered the strain relaxation. An overgrowth InGaN layer was found to help relieving the strain in InGaN quantum dots by introducing misfit dislocations. The defects were observed in low temperature GaN layers which suggested the existence of stacking faults around InGaN QDs.